Analyzing Audit Quality: Experience, Motivation, Audit Fees with Auditor Ethics as Moderator - Abrar, Nur Alfira; Tjan, Julianty Sidik; Ikhtiari, Kirana (Advances in Managerial Auditing Research, 2023)
Purpose: This study examines the influence of auditor experience, motivation, and audit fees on audit quality, with auditor ethics as a moderating variable in public accounting firms (KAP) in Makassar. Research Design and Methodology: This quantitative study collected primary data through questionnaires distributed to 46 auditors from 9 public accounting firms in Makassar. The population consisted of all auditors registered with these firms. Hypotheses were tested using multiple linear regression analysis with the assistance of Smart PLS 3.0 software. Findings and Discussion: The results revealed that auditor experience, motivation, and audit fees significantly and positively influence audit quality. Additionally, auditor ethics was found to significantly moderate the relationship between auditor experience and audit fees with audit quality. However, the moderation effect of auditor ethics on the relationship between auditor motivation and audit quality was negative and insignificant. These findings suggest that while experience and appropriate compensation enhance audit quality, motivation alone may not be sufficient without ethical reinforcement. Implications: The study highlights the importance of ethical practices in enhancing audit quality, suggesting that public accounting firms should focus on continuous training, fair compensation, and strengthening ethical frameworks. Future research could explore the impact of technological advancements and remote auditing on audit quality and auditor ethics.